The geometric correction procedure using topographic map versus GPS-derived ground control points for Lulc analysis - Yasin, Muhammad Yazrin; Hj. Mohd. Noor, Norzailawati; Mohd Yusof, Mariney; Abdullah, Jamalunlaili (2020)
Precision measurement of land use land cover change detection is essential for urban growth assessment. Remote sensing imagery provide an integrated monitoring of the temporal changes of urban growth. Accurate geometric correction relies largely on accurate rectification of the remotely sensed data to produce classified thematic changes maps. The study utilised data from Landsat 5, 7 and 8. The rectification process involves two sources of references which are the digitized topographic map and the ground control points acquired using Global Positioning System (GPS). The study attempts to compare which sources produce higher rectification accuracy. Topographic map is acquired from the Department of Survey and Mapping Malaysia with 1:10,000 scale, 5 meters contour line and rectified skew orthomorphic grid projection. Ground truthing utilised Android 10.36.0 GPS WGS84 capability smartphone. The study found the ground control points acquired using smartphone with GPS capability were much more accurate to those acquired from topographic maps. Root-mean-square error (RMSe) of the GPS-derived control point, source point and correction point show higher accuracy results acquired from ground truthing.